A bibliometric examination of global port facility research propagation (1975 - 2023) - Salihu Adam Jiddah; Suhaila Abdul Hanan; Nur Khairiel Anuar (Asian Journal of Shipping and Logistics (AJSL), 2024)
Seaports play a crucial role in international trade and economic development. This study aims to analyze the existing literature on port facilities to identify research patterns and emerging areas of interest. Using the Scopus database, the researchers searched for publications related to port facilities and found a total of 178 scholarly articles. The data was analyzed using Microsoft Excel, Publish or Perish and VOS viewer. The study examined subject areas, keywords, citations, and Journal/publishers metrics, to understand the key contributors and collaborative efforts in this field. The findings revealed a lack of scholarly evaluation of port facilities literature until 1975. From 1975 to 2003, there were 57 publications with very few citations. However, interest in this field grew significantly between 2004 and 2023, with 114 publications and 496 citations. Most of the documents were written in English, and there was concentration of research efforts in specific areas. International collaboration was observed among 12 countries. The study suggests the need for more research, collaborations, and citations in the field of port facilities, particularly in areas beyond engineering and earth and planetary sciences. Logistics management, computing, and maritime should be further explored to address gaps in the current literature.
Keywords: 650; Bibliometric; Journal metrics; Port facilities; Research focal points; Scopus database